Cocaine Self-administration and Extinction Inversely Alter Neuron to Glia Exosomal Dynamics in the Nucleus Accumbens - Jarvis, Rachel; Tamashiro-Orrego, Alessandra; Promes, Vanessa; Tu, Leona; Shi, Jinyuan; Yang, Yongjie (Frontiers in Cellular Neuroscience, 2020)
Alteration of glutamatergic synaptic plasticity in the Nucleus Accumbens (NAc) has been implicated in cocaine seeking behaviors. Astroglial mechanisms for maintaining extracellular glutamate homeostasis through cysteine/glutamate exchanger (xCT) and glutamate transporter GLT1 are dysregulated following cocaine exposure and contribute to altered glutamatergic synaptic plasticity. However, how these astroglial proteins become dysregulated in cocaine addiction remains unknown. We recently showed that neuron to astroglial exosome signaling is essential to maintain GLT1 protein expression by transferring neuronal miR-124-3p into astrocytes to suppress GLT1-inhibting miRs in astrocytes. In the current study, by selectively labeling neuronal exosomes using CD63-GFPf/+ exosome reporter mice, we examined how the self-administration and extinction stages of the mouse cocaine self-administration model alter neuronal exosome signaling to astrocytes and microglia in the NAc. We found that cocaine (but not food) self-administration strongly reduces internalization of neuronal exosomes, particularly in astrocytes in the NAc (but not in motor cortex), which can be effectively reversed by extinction training. In parallel, cocaine self-administration alone specifically and differentially affects activation of glial cells by decreasing GFAP expression in astrocytes but increasing Iba1 expression in microglia. However, extinction training fully reverses the increased Iba1 expression in microglia but only partially reverses the reduction of GFAP in astrocytes. Taken together, our study reveals altered in vivo dynamics of NAc neuronal exosomes in the cocaine addiction model, providing new insights about how altered neuron to glial exosome signaling may contribute to astroglial dysfunction in cocaine addiction.